The Nature of Crisis in Enterprise Activities - Kozachenko Ganna V.; Naden Ganna O. (Problemi Ekonomiki, 2017)
It is shown that the concept of enterprise anti-crisis management and its components should be based on the nature of crisis in enterprise activities, the idea of which is the fundamental basis of enterprise anti-crisis management and determines its object, subject, tasks, main guidelines and vectors. Examples of defining the concept “crisis in enterprise activities”, which testify to the lack of unity of views on its content, are given. There revealed the attributive nature of crisis in enterprise activities, according to which a crisis, being an attribute of the system “enterprise”, begins intensifying under the influence of driving forces and individual factors, which is identified by presence of disruptions in the performance by the enterprise of its functions. There substantiated the expediency of singling out manifestations of crisis in enterprise activities (crisis phenomena, crisis situation and crisis state) depending on the level of disruptions in the performance by the enterprise of its functions, which is of great importance for determining the tasks of enterprise anti-crisis management. The crisis cycle in enterprise activities in any of its manifestations is analysed, features of the cycle are considered.